2014
DOI: 10.3892/ijo.2014.2704
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 regulates cyclin G2 expression and plays an oncogenic role in laryngeal squamous cell carcinoma

Abstract: microRNA93 (miR-93) is expressed in the miR‑106b-25 cluster, located in intron 13 of the MCM7 gene. Our previous study found that miR-93 was significantly upregulated in laryngeal squamous cell carcinoma (LSCC), and cyclin G2 (CCNG2) was a potential target of miR-93 in LSCC. However, the possible functions and molecular mechanisms of miR-93 in LSCC remain unknown. In the present study, we show that the level of CCNG2 protein expression was significantly lower in LSCC cancer tissue than normal tissues. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…miR-93-5p has been documented to play a role as an oncogenic miRNA in many tumor types [6466], but has not been investigated in NB. miR-93-5p is hosted in MCM7, which is regulated by MYCN, and is also predicted to target MYCN (confidence score: 1.0).…”
Section: Resultsmentioning
confidence: 99%
“…miR-93-5p has been documented to play a role as an oncogenic miRNA in many tumor types [6466], but has not been investigated in NB. miR-93-5p is hosted in MCM7, which is regulated by MYCN, and is also predicted to target MYCN (confidence score: 1.0).…”
Section: Resultsmentioning
confidence: 99%
“…28 MiR-93 was also reported to function as a tumor promoter via regulating diversity of tumor-suppressor genes such as NRF2, 29 Dab2 30 and cyclin G2. 31 More interestingly, certain researches revealed that either miR-106b or miR-93 could directly target one common gene named PTEN in many other cancers. 32, 33 In our research, we found that PTEN was the direct target of both miR-106b and miR-93.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic function of miR-93 is also reported in prostate cancer, ovarian cancer, lung cancer, head and neck squamous cell carcinoma, and non–small cell lung cancer [41], [42], [43], [44], [45]. It is also documented that miR-93 promotes glioma through regulation of AKT and IL8 [46].…”
Section: Discussionmentioning
confidence: 85%